The experience of persistent pain and quality of life among women following treatment for breast cancer: An attachment perspective. Issue 10 (31st August 2018) - Smith, Michelle D.; Meredith, Pamela J.; Chua, Siong Yin
Abstract: Objectives: The aims of this study were to investigate associations between attachment and the presence of persistent pain in women following treatment for breast cancer and to investigate the relationship between attachment, pain, and quality of life (QOL) in women with persistent pain. Methods: Women ( N = 335) previously diagnosed with primary non‐metastatic breast cancer completed an online survey with measures of attachment, pain, QOL, demographics, and medical history. Variables were compared between women with ( N = 128) and without ( N = 207) persistent pain. For those reporting pain, regression analyses were conducted to investigate relationships between attachment, pain, and QOL. Results: Higher attachment anxiety, but not attachment avoidance, was related to the presence of persistent pain. Among women with persistent pain, associations between attachment anxiety and avoidance and greater pain intensity were lost when pain catastrophizing was considered in analysis. Significant associations between attachment and diminished QOL and perceived effectiveness of pain management were identified in multivariate analysis. Conclusions: These findings extend the available literature regarding associations between pain and attachment insecurity. In women with pain after breast cancer treatment, attachment anxiety and avoidance were associated with negative pain and QOL outcomes. Further attention regarding the use of attachment‐informed approaches in supporting women following breast cancer treatment is indicated.